Kepemimpinan Sekolah Islam Terpadu di Minoritas Muslim Papua Barat - Ismail Suardi Wekke; Siarni Siarni; Nuryantika Nuryantika (Akademika: Jurnal Keagamaan dan Pendidikan, 2016)
One of obstacle to enjoy ideal Islamic education in the minority Muslim region is there is no excellent educational institution is running in the area. Therefore, some Muslim family should send their children to study outside the city. Unfortunately, not every family could reach the way. One of the initiative to establish Islamic education which to convey integrated education was in Sorong city of West Papua. The case study was conducted in SDIT Al-Izzah, Sorong. Non-participant observation and in-depth interview were conducted to collect data. The primary school was started on 2006. The program is similar with other national school of the nation. In addition, religious subjects were integrated to the curriculum in enhancing Muslim understanding. They launched Quranic Based Green School. This program to accelerate school program with Quranic values rooted. Moreover, the school was supported through leadership and team work. The team work conserve the program from side to side and maintain from the concept to the program. Finally, this paper concludes that Muslim minority enjoy the opportunity to launched educational institution. They have a wide range chance in educating Muslim society. Nowadays, the school lengthens to the senior high school after a countless successful development.